Is there a correlation between arthroscopic findings and the clinical signs and symptoms of patients with internal derangement of the temporomandibular joint? A prospective study - Sato, F. R.L. [UNESP]; Lima, C. A.A.; Tralli, G.; da Silva, R. A. (Elsevier, 2018)
The aim of this study was to evaluate the correlation between clinical signs and symptoms of patients with internal derangement of the temporomandibular joint (TMJ) and arthroscopic findings. The study included a sample of 67 patients who underwent TMJ arthroscopy. The variables evaluated were the arthroscopic findings of synovitis, chondromalacia, adhesion, and roofing. The Spearman correlation index was used to correlate these findings with the clinical signs and symptoms of internal derangement of the TMJ, namely maximum mouth opening, pain (visual analogue scale, VAS), and the Wilkes classification. The mean age of the population was 36.16 years, and 85% were female. There was a correlation between pain and synovitis (P = 0.0029, r = 0.3508), between mouth opening limitation and the amount of adhesion (P = 0.0004, r = −0.4084), and between Wilkes classification and the presence of chondromalacia and disc displacement (P = 0.001, r = 0.374 and P = 0.0045, r = −0.3357, respectively). No correlation was found between age and the presence of chondromalacia (P = 0.3444, r = 0.1147). Patients who had worse pain symptoms had more advanced stages of synovitis, and the increased presence of adhesions was associated with limitations in mouth opening. Furthermore, those with more advanced Wilkes stages had greater disc displacement and more severe stages of chondromalacia.
Keywords: arthralgia; arthroscopy; synovitis; temporomandibular dysfunction; temporomandibular joint; trismus